Non-profit organizations as the subjects of socio-economic development of the regions in the Volga Federal District (data taken from the Presidential Grants Fund) - Dinara Vitalievna Nekrasova; Mikhail Aleksandrovich Mukhin; Anna Alexandrovna Urasova (Вестник Пермского университета: Серия Экономика, 2023)
Introduction. Recent decade, attention to the third sector of the economy has increased. Non-profit organizations which used to be companies with targeted assistance are increasingly becoming full-fledged subjects of socio-economic processes, partners of public authorities, and local self-government in solving socially significant issues. Their specialized activities make them a source of innovations in the social sphere, generate new options for solving various problems, and the chance to attract grant or charitable funds to solve such problems and to lower the burden on municipal and regional budgets. This actually turns out to be almost the only funding source for measures to address social problems at the deficit budget territories.